Beginning BlackBerry Development - Rizk, Anthony (Apress, 2012)
There has never been a better time to develop applications for BlackBerry devices than right now. Since Research In Motion (RIM) launched the first models almost a decade ago, the BlackBerry smartphone has gone from relative obscurity to near universal visibility—think about how commonplace it has become to see people in airports, hotels, offices, or just about anywhere stealing a few minutes to check their e-mail or type replies. The BlackBerry software development kit has been around since the first devices were released and has grown to include an extensive collection of examples, documentation, and a mature set of APIs and tools that have opened the door for all kinds of great applications, most of which only currently exist in someone’s imagination. And with the maturing of the BlackBerry community and the introduction of BlackBerry App World, it’s easier than ever to get your application noticed and downloaded by users worldwide.